Comparison of the effects between two accesses for the treatment of arteriovenous fistula stenosis or occlusion - CHEN Hao; LIU Juan; LIU Yun (Linchuang shenzangbing zazhi)
Objective To study the effectiveness and safety of the two different puncture ways of ultrasound guided distal radial artery access and proximal reversal head vein flow access for the treatment of autogenous arteriovenous fistula（AVF） stenosis or occlusion. Methods Sixty-three patients with AVF stenosis or occlusion, undergoing perctuaneous transluminal angioplasty（PTA） under the guidance of ultrasound in Chengdu Fifth People’s Hospital and Chengdu Fist People’s Hospital from August 2016 to November 2017, were selected. In the course of treatment, patients were divided into two groups according to the allocation of the single and even numbers of hospital beds. Different puncture ways that is, ultrasound guided distal radial artery access（artery group） and proximal reversal head vein flow access（vein group）, were adopted to conduct the surgery for the patients. The success rate, complications and phase 1 patency rate within 1 year in the two groups were calculated and compared. Results The incidence of complications（21.88%） in arterial group was higher than that in the vein group（9.68%）, but comparison between the two groups showed no statistically significant difference（P>0.05）. The guide wire overpass rate in the artery group was comparable to that in the vein group. There were no significant difference between the two groups（both P>0.05）. The phase 1 overpass rates at the 3th, 6th, 9th and 12th months after the surgery were 100.0%, 83.87%, 77.42% and 70.97% in the arterial group. They were 100.0%, 80.77%, 76.92%, 73.07%, respectively, in the vein group. There was no significant difference in the phase 1 patency rate between the two groups（P>0.05）. Conclusions The ultrasound-guided distal radial artery access for treatment of AVF stenosis or occlusion may be used as an important access for PTA to treat AVF stenosis or occlusion, due to high guide wire overpass rate and good post-operative patency.